2007
DOI: 10.1051/alr:2008001
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-linked acoustic receivers to observe behavior of fish in remote areas

Abstract: Automated acoustic receivers are now widely used by biologists to study the behavior of fish. However, currently available acoustic receivers require physical recovery of the units to download stored data. Such operation is often difficult in remote study areas like in the open ocean. We present a new satellite-linked acoustic receiver (Vemco VR3-Argos) that allows downloading data through a satellite uplink (Argos). The VR3-Argos can last up to one year, sending GPS positions and tag data at regular time inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 15 publications
2
30
2
3
Order By: Relevance
“…On drifting FADs in the Indian Ocean, Dagorn et al (2007b) observed a mean CRT of 0.9 days. We have shown that individuals of the same size and same species (skipjack tuna) can display different CRTs at the same FAD at different times.…”
Section: Discussionmentioning
confidence: 93%
“…On drifting FADs in the Indian Ocean, Dagorn et al (2007b) observed a mean CRT of 0.9 days. We have shown that individuals of the same size and same species (skipjack tuna) can display different CRTs at the same FAD at different times.…”
Section: Discussionmentioning
confidence: 93%
“…Acoustic receivers are also available from manufacturers of telemetry equipment where data can be transferred from a floating surface buoy to shore-based modem (computer or telephone system) as radio signals, or to ARGOS satellites (Dagorn et al, 2007).…”
Section: How To Record Fish Tagged With Radio and Acoustic Transmittersmentioning
confidence: 99%
“…The former is composed of a variety of receivers, a mooring within the river, a submersible cable, a circuit board, modem, and battery enclosed within a waterproof box, with a cable leading from it to an array of solar cells. This is an emerging capability, which has recently been used in remote area of the ocean to monitor the residence times and depth preferences of four species fishes at a fish aggregating device (FAD) [7].…”
Section: Introductionmentioning
confidence: 99%